Variation in milk minerals and chemical components corresponding to milking time and lactation day in sows. Issue 8 (16th November 2020) - Long, Jifei; Guo, Songge; Cai, Lichuang; Zhang, Tianyong; Chen, Wenbin; Xie, Chunyan
ABSTRACT: This study aimed to evaluate the variation of milk mineral and chemical components in colostrum and milk corresponding to milking time and lactation day. Samples were collected at 1, 7, 14 and 21 days postpartum, and the effects of milking time (diurnal milk/nocturnal milk) on mineral and chemical components were studied. Results showed that the mineral levels, as well as fat, protein, lactose and total solid, were significantly affected ( P  < 0.01) by lactation day. The content of Na, K, Ca, and the ratio of Na/K were affected ( P  < 0.05) by milking time on day 7 and 14 of lactation, whereas this effect was inconclusive for the other days. Chemical components were not affected by milking time, although the proportion of total solids in the milk tended to decrease (0.05 <  P  < 0.10) in nocturnal milk on day 14 of lactation. Significant correlations were observed among milk minerals or chemical components ( P  < 0.05), although there were slight correlations between milk mineral and chemical component. These findings showed that milk minerals and chemical components in sows could be affected by milking time and lactation day to some extent, which may provide a reference for milking parameters.